A Programmable Expander for Patients With Cleft Lip and Palate. (July 2019) - Torres, Ana; AlYazeedy, Ibtesam; Yen, Stephen
This report describes a method to expand cleft segments of patients with cleft lip and palate prior to the secondary alveolar bone graft (ABG) using a reprogrammable nickel titanium expander. The expander can be reprogrammed with electric current to the desired width for each patient and delivers a gradual slow expansive spring force that expands and aligns the segments without further adjustments. Reprogramming the expander eliminates the need for multiple appliances and reduces chair time and patient appointments. The expander can be left in place during the ABG, because it does not interfere with a palatal flap. This alternative approach may be useful for patients who travel long distances to obtain cleft-related care.